Development of a method for the quantitative determination of glibenclamide in tablets - L. H. Leleka; S. O. Vasuik (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2023)
Aim. To develop and validate a spectrophotometric technique for quantitative determination of glibenclamide in tablets by reaction with 2,3-dichloro-1,4-naphthoquinone.